The collaborative evolution of trust, information flow, and social cooperation: a study on network stability based on dynamic game models - Liu Weiqi; Yan Jun; Xiao Jieyu (Scientific Reports)
Abstract Human society is organized around individual actors. When making behavioral choices, individuals engage in rational deductions based on their environment and select the ‘most appropriate’ actions. This paper introduces a social relations network information system that enables behavior nodes and their environments to observe behaviors and assign scores accordingly. The findings of this study indicate that: (1) during the process of network formation, nodes exhibit a tendency toward pro-social cooperative behavior; (2) nodes exhibit different behavioral patterns during different processes of network formation; and (3) ordinary nodes that do not actively participate in interactions also contribute to the transmission of social network information, demonstrating that every social individual serves as a node for information dissemination.